(MnzFe1—z)yOx combined oxides as oxygen carrier for chemical‐looping with oxygen uncoupling. Issue 2 (7th June 2012) - Azimi, Golnar; Rydén, Magnus; Leion, Henrik; Mattisson, Tobias; Lyngfelt, Anders
Abstract : Oxygen carrier particles with the composition (Mn0.8, Fe0.2 )2 O3 were found to readily release gas phase oxygen at 850°C, and were capable to oxidize CH4 completely and convert wood char rapidly to CO2 during experiments in a batch fluidized bed reactor. The particles were able to release oxygen corresponding to more than 3% of their mass in less than 40 s. Because of the low price and favourable environmental properties of manganese and iron oxides, this finding could be of great importance for the development of chemical‐looping combustion with oxygen uncoupling. © 2012 American Institute of Chemical Engineers AIChE J, 59: 582–588, 2013